Conceptual Of Targhib In Social Exchange Theory - Rita Andini; Dwi Retna Sulistyawati; Tri Handayani; Heri Poerbantoro; Sukamto Sukamto (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This study tries to explore the overall concept of targhib, namely that there are four factors that are used in shaping the performance of an Islamic organization (ta'awun/help, as-samahah/tolerance, friendship, ukhuwah, tawadhu') as a rule in conducting interactions both individually and collectively. group. In the concept of targhib, it functions to motivate humans as individuals and groups in small and large organizations, as was done by the Prophet Muhammad at the beginning of preaching activities. Rasulullah SAW encouraged us humans with the promise of reward and Jannah, for anyone who is able to walk according to the creed of monotheism and far from polytheism by carrying out the values ​​of ta'awun / help, as-samahah / tolerance, friendship, ukhuwah, tawadhu' in organizing. Tafsir Ibnu Katsir, (2013) explains targhib is a certainty of comfort, pleasure in the hereafter which is done with seduction. This concept refers to human nature, which has the desire to always live in a state of pleasure, safety and away from difficult or suffering conditions.